From Curriculum to Classroom Practice: A Case Study of a STEAM Learning Ecosystem for Fostering Students’ Computational Thinking - Alma Azrel Pamula; Purnomo Purnomo (CV. Creative Tugu Pena, 2025)
This study explores how a Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning ecosystem fosters computational thinking among seventh-grade students at Mega Islamic Boarding School Semarang by examining the relationship between curriculum sequencing, classroom practices, and institutional support. A qualitative single-case study was conducted over six weeks. Data were collected through semi-structured interviews with the vice principal for curriculum and one STEAM teacher, two non-participant classroom observations involving 13 students, analysis of the seventh-grade STEAM curriculum, and school documentation. The data were analyzed thematically using deductive and inductive coding, including the mapping of STEAM dimensions across classroom activities and school projects. The findings revealed three interconnected themes. First, the curriculum introduced computational thinking concepts before programming activities. Second, coding practices were facilitated through teacher explanation, independent practice, feedback, peer assistance, and repeated attempts. Third, digital facilities, teacher involvement in curriculum development, and project exhibitions supported the continuity of the STEAM program. The STEAM mapping showed that Technology, Engineering, and Mathematics were more visible in coding activities, whereas Science and Arts appeared more prominently in project-based activities. These findings indicate that computational thinking is facilitated not by coding alone, but through an interconnected ecosystem linking curriculum design, classroom practice, and institutional support.